Camp‐based psychosocial intervention dosage and changes in independence in young people with spina bifida. (13th April 2019) - Driscoll, Colleen F Bechtel; Murray, Caitlin B; Holbein, Christina E; Stiles‐Shields, Colleen; Cuevas, Gina; Holmbeck, Grayson N
Abstract : Aim: To examine associations between camp‐based intervention dosage and changes in independence‐related skills for young people with spina bifida. Method: Participants were 110 individuals (mean age [SD] 14y 7mo [6y 1mo], range 6–32y; 66 females, 54 males) who attended a summer camp for individuals with spina bifida between 2 to 6 times (mean 2.40; operationalized as 'dosage'). Parents of young campers (e.g. those <18y) also participated in data collection. Campers and/or parents completed preintervention measures assessing campers' level of medical responsibility, mastery over medical tasks, and social skills. Outcomes included change in preintervention scores from dose 1 to final dose. Results: Hierarchical regression analyses with and without covariates (age, IQ, and lesion level at dose 1) revealed that increased dosage was significantly associated with greater parent‐reported improvements in campers' medical responsibility and mastery over medical tasks. Increased dosage was also significantly associated with camper‐report of increased medical responsibility, but this relationship was no longer significant when including covariates. Intervention dosage was not associated with changes in campers' social skills. Interpretation: Repeated participation in a camp‐based intervention was associated with improvements in condition‐related independence. Future work may focus on the development of interventions to promote improvements in social skills for young people with spina bifida. What this paper adds: Participating in an intervention over multiple summers is associated with increases in campers' responsibility for spina bifida‐related tasks. Repeated summer camp intervention participation is associated with improved mastery over condition‐related tasks for campers with spina bifida. Repeated camp intervention participation is not associated with changes in social skills for campers with spina bifida. What this paper adds: Participating in an intervention over multiple summers is associated with increases in campers' responsibility for spina bifida‐related tasks. Repeated summer camp intervention participation is associated with improved mastery over condition‐related tasks for campers with spina bifida. Repeated camp intervention participation is not associated with changes in social skills for campers with spina bifida. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Moola et al. on page 1355 of this issue. Video Podcast: https://www.youtube.com/watch?v=caxzziwo9Fw Resumen: Dosis de intervención psicosocial en campamentos recreativos y cambios en la independencia en jóvenes con espina bífida: Objetivo: Examinar las asociaciones entre la dosis de intervención recibidas en campamentos recreativos y los cambios en las habilidades relacionadas con la independencia de los jóvenes con espina bífida. Método: Los participantes fueron 110 individuos (edad media [DS] 14 años 7 meses[6y 1 mes], rango 6–32 años; 66 mujeres, 54 varones) que asistieron a un campamento de verano para personas con espina bífida, con una frecuencia entre 2 a 6 veces (media 2, 40; considerada como 'dosificación' de la intervención). Los padres de los jóvenes que concurrieron a los campamentos (por ejemplo, aquellos con <18 años) también participaron en la recopilación de datos. Los participantes y / o los padres completaron las escalas previas a la intervención evaluando el nivel de responsabilidad sobre su salud de los participantes, el dominio sobre las tareas sanitarias y las habilidades sociales. Los resultados incluyeron cambios en las puntuaciones preintervención de la primera dosis a la última dosis. Resultados: Los análisis de regresión jerárquica con y sin covariables (edad, coeficiente intelectual y nivel de lesión) revelaron que el aumento de la dosis se asoció significativamente con mayores mejoras informadas por los padres en la responsabilidad sobre su salud de los participantes y el dominio sobre las tareas sanitarias. El aumento de la dosis también se asoció significativamente con el informe de instructores reportando mayor responsabilidad sobre su propia salud, pero esta relación ya no fue significativa al incluir las covariables. La dosis de la intervención no se asoció con cambios en las habilidades sociales de los participantes Interpretación: La participación repetida en una intervención recibida en el campamento se asoció con mejoras en la independencia relacionada con la condición de salud. El trabajo futuro podría centrarse en el desarrollo de intervenciones para promover mejoras en las habilidades sociales de los jóvenes con espina bífida. Abstract : Dosagem de intervenção psicossocial baseada em acampamento e mudanças na independência de jovens com espinha bífida: Objetivo: Examinar associações entre dosagem de intervenção baseada em acampamento e mudanças nas habilidades relacionadas à independência para jovens com espinha bífida. Método: Participaram 110 indivíduos (idade média [desvio padrão] 14 anos e 7 meses [6 anos e 1 mês], 66 mulheres e 54 homens) que participaram do acampamento de verão para indivíduos com espinha bífida entre 2 e 6 vezes (média de 2, 40; operacionalizado como `dosagem`). Os pais de jovens campistas (por exemplo, os <18 anos) também participaram da coleta de dados. Campistas e/ou pais completaram medidas de pré‐intervenção avaliando o nível de responsabilidade médica dos campistas, domínio sobre tarefas médicas e habilidades sociais. Os resultados incluíram a mudança nos escores pré‐intervenção da dose 1 para a dose final. Resultados: Análises de regressão hierárquica com e sem covariáveis (idade, QI e nível de lesão na dosagem 1) revelaram que o aumento da dosagem foi significativamente associado a maiores melhorias relatadas pelos pais na responsabilidade médica dos campistas e no domínio de tarefas médicas. O aumento da dosagem também foi significativamente associado ao relato por parte do campista de maior responsabilidade médica, mas essa relação não era mais significativa quando se incluíam covariáveis. A dosagem de intervenção não foi associada a mudanças nas habilidades sociais dos campistas. Interpretação: A participação repetida em uma intervenção baseada em acampamento foi associada a melhorias na independência relacionada à condição. Trabalho futuro pode se concentrar no desenvolvimento de intervenções para promover melhorias nas habilidades sociais para jovens com espinha bífida.